2013
DOI: 10.11144/javeriana.upsy12-5.gcad
|View full text |Cite
|
Sign up to set email alerts
|

Gaze-cueing of attention distorts visual space

Abstract: A briefly presented peripheral flash is often mislocalized with a bias toward an attended object. The target mislocalization has been ascribed to the integration of location signals between a target and an attended object, and this results in the mislocalization of the target toward the attended object. It was unclear whether external objects that attract observer's attention were necessary to cause the target mislocalization. This study aimed at examining whether the target mislocalization occurred when the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…For instance, it appears that endogenous cues most reliably result in repulsion effects when placeholders are present in the array to help guide attention to a specific location in the visual field (Lawrence et al, 2020). Given the uncertainty regarding the effects of endogenous cues, the effects of symbolic arrow cues on the ARE remain unknown (although the effects of gaze cueing have been tested; see Yamada & Kawabe, 2013). This lack of research is surprising as previously observed effects of symbolic knowledge on performance using traditional cueing tasks may not have been due to shifts of attention.…”
Section: Attentional Repulsionmentioning
confidence: 99%
“…For instance, it appears that endogenous cues most reliably result in repulsion effects when placeholders are present in the array to help guide attention to a specific location in the visual field (Lawrence et al, 2020). Given the uncertainty regarding the effects of endogenous cues, the effects of symbolic arrow cues on the ARE remain unknown (although the effects of gaze cueing have been tested; see Yamada & Kawabe, 2013). This lack of research is surprising as previously observed effects of symbolic knowledge on performance using traditional cueing tasks may not have been due to shifts of attention.…”
Section: Attentional Repulsionmentioning
confidence: 99%
“…Cues appearing on the right-hand side of the screen caused the line to appear shifted leftwards and vice versa. Yamada, Yuki, and Kawabe (2013) Attraction and repulsion effects were tested using a gaze cueing procedure. Participants were required to determine whether two circles appearing at the cued location were vertically offset.…”
Section: Ono and Watanabementioning
confidence: 99%